INFLUENCE OF LEADERSHIP BEHAVIOR, INTRINSIC MOTIVATION, AND ORGANIZATIONAL CITIZENSHIP BEHAVIOR ON WORK ENGAGEMENT OF SECURITY EMPLOYEES OF PT BUMI DAYA PLAZA IN JAKARTA - Rofie Anggritantyo, Mohamad; Singmin Johanes Lo (Dinasti International Journal of Digital Business Management, 2022)
The purpose of this research is to analyze the effects of leadership behavior, intrinsic motivation, organizational citizenship behavior on work engagement. The subjects of this research are the security employees of PT Bumi Daya Plaza, Jakarta. The purposive sampling technique is used for securities who have been working for two years and more. They are 100 security employees become respondents. This research uses a quantitative approach using questionnaire. Data are analyzed using Multiple Linear Regression with the help of SPSS version 21.0. for Windows. The results of this study indicate that both leadership behavior and organizational citizenship behavior positively and significantly influence work engagement; meanwhile, intrinsic motivation does not significantly influence work engagement. It is suggested that to increase work engagement the top management should pay attention to improve the securities work methods, increase obedience to company rules and policies, and participate in company activities.